2020
DOI: 10.1038/s41467-019-13993-7
|View full text |Cite
|
Sign up to set email alerts
|

U1 snRNP regulates cancer cell migration and invasion in vitro

Abstract: Stimulated cells and cancer cells have widespread shortening of mRNA 3'-untranslated regions (3'UTRs) and switches to shorter mRNA isoforms due to usage of more proximal polyadenylation signals (PASs) in introns and last exons. U1 snRNP (U1), vertebrates' most abundant non-coding (spliceosomal) small nuclear RNA, silences proximal PASs and its inhibition with antisense morpholino oligonucleotides (U1 AMO) triggers widespread premature transcription termination and mRNA shortening. Here we show that low U1 AMO … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

161
4,036
17
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 8,732 publications
(4,217 citation statements)
references
References 60 publications
161
4,036
17
3
Order By: Relevance
“…snRNAs might have important functions in cancer development and progression, as well as in drug resistance [3]. For instance, U1 snRNP could regulate cancer cell migration and invasion in vitro [52]. Nonetheless, further investigation of the multiple ncRNAs whose changes exist in bronchial epitheliums would be important to understand the mechanism of field cancerization in lung carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…snRNAs might have important functions in cancer development and progression, as well as in drug resistance [3]. For instance, U1 snRNP could regulate cancer cell migration and invasion in vitro [52]. Nonetheless, further investigation of the multiple ncRNAs whose changes exist in bronchial epitheliums would be important to understand the mechanism of field cancerization in lung carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In Hubei, because the model captured most of the epidemic first wave, the predicted number and timing of deaths could be compared with later reports of SARS-CoV-2 deaths, providing some degree of external validation (S1 Text, section 4). Third, our model is stratified by age group, which has been shown as a crucial feature for modeling emerging respiratory infections [24]. Fourth, the model uses surveillance data that can be collected routinely, and it does not require individual-level data or studies in the general population.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…The results show that knockdown of lncRNA SLC8A1-AS1 leads to reduced cell proliferation in vitro, and in vivo data suggest that it is a potential molecular target for therapy. Cell migration and invasion are signi cant aspects of cancer progression [17], we found that inhibit the expression of lncRNA SLC8A1-AS1 can inhibited the migration and invasion of U87MG and LN382 cells signi cantly. EMT is a critical biological process in tumor cell migration and invasion [18].…”
Section: Discussionmentioning
confidence: 75%